Silicon uptake by selected plant species, and its role in growth promotion and basal stem rot resistance in palms - Jamaludin, Nurul Mayzaitul Azwa (2015)
Silicon (Si) is the second most abundant and beneficial element for plant growth in higher plants. The differences in Si accumulation have been attributed to the Si absorbing ability of the roots. The most important aspect in this research is to make full use of the role of Si in conferring tolerance in plants against stresses. Thus, the goals of this research were: (i) to investigate the role of individual root and root system in Si uptake by selected plant species, and (ii) to assess the effects of GanoCareTM NRICH OCSpecial 1 (OCS 1) on vegetative growth and reducing the risk of Ganoderma disease in palms seedlings. To reveal the ability of root to take up Si, the study was conducted using the hydroponic culture system with modified Hoagland’s nutrient solution containing different amount of Si. The results showed that the Si uptake was higher in the root- than shoot-part of mangroves and oil palm under study with the values of 51.8% and 38.2%, respectively. In contrast, betel nut palms uptake 32.4% more Si in the shoot-than root-parts. The Si uptake per root dry matter and Si uptake per 4 cm of root was higher in mangroves than in oil palms and followed by betel nut palms. Based on the ability to take up Si, the different oil palm progenies and clones in the study were clustered using Jaccard Similarity Coefficient into 5 groups. The vegetative growth and selected physiological parameters of oil palm and betel nut palm seedlings and the effectiveness of OCS 1 (6: 6: 8: 2 + GanoCareTM) against basal stem rot (BSR) disease caused by Ganoderma boninense was performed under nursery condition. Results showed that the T2-seedlings of oil palm increased the total number of fronds (11.8%), seedlings height (15.4%), rachis length (9.3%), girth size (24.4%), chlorophyll content (10.2%), photosynthesis rate (21.0%), leaf area index (27.3%) and total biomass (18.3%) compared to control. Application of OCS 1 to betel nut palm seedlings increased the total number of fronds, seedlings height, rachis length, girth size, chlorophyll content and total biomass to more than 16.7, 12.3, 13.4, 31.3, 14.8 and 30.2%, respectively. The DI of oil palm (50.0%) and betel nut palm (44.4%) for T3-seedlings were significantly different (p≤0.05) compared to T2-seedlings with both values of 94.4%. The BSR disease incidence in oil palm and betel nut palm of T3- seedlings were reduced 52.6% and 67.4%, respectively. This supports the contention that the beneficial element in GanoCareTM may provide protection against Ganoderma infection in both palms. The results confirmed that an individual root and root system in selected plants’ play an important role in response to Si uptake ability. The higher uptake of Si in root-parts may provide good indicator for the plant to be resistant against root-infecting organisms. Hence, the addition of OCS 1 had successfully enhanced the growth and reduced the BSR disease in palm seedlings.